Correlation between Child Behavior and Depression in Mother with Autism Spectrum Disorders Child - Kido, Kumiko; Fujita, Kumi (Journal of Maternal and Child Health, 2021)
Background: The behavioural characteristics of an autistic child can lead to challenging relationships with the mother. For mothers who serve as the key person in the care of their children with ASD, maintaining good mental health, which may be directly related to the growth and development of their children, is an important issue for professionals engaged in parenting support. The aim of this study was to determine the interaction between the behavioural problems of children with ASD (from toddlers to adolescents) and their mothers’ depression. Subjects and Method: This was a cross-sectional study carried out in Yamaguchi Prefecture, Japan. The recruitment of subjects was through a paediatric out-patient unit. Eighty-six mothers with ASD participated in this observational study. The Center for Epidemiological Studies-Depression (CES-D) scale was used as a measure of depression in mothers, and the Child Behaviour Checklist (CBCL) was used as an assessment of the children’s behavioral characteristics. The prevalence of depression among mothers of children with ASD was estimated and related factors were also examined. Results: There were 66 boys (76.7%), 12 girls (14.0%) and 8 (9.3%) non-responders. Comparing the pre- adolescent and adolescent groups, there were significant differences in the ages of mothers and children (P <0.001). In this study, the prevalence rate of depression in mothers of children with ASD was 47.7% (95% CI= 36.8 to 58.7), and the prevalence rate of depression in mothers of adolescent children group was 48.6% (95% CI= 31.4 to 6.0). The predictive factors of maternal depression were others’ problems (toileting problems, and masturbation) in CBCL and children’s age group. Conclusion: These children’s behavioural characteristics were recognised as serious problems by their mothers, which in turn can negatively affect their mental health, particularly the depression of mothers in the adolescent group was probably due to concerns about their children’s unsocial behaviour.